The consequence of CO2 acidification in the harmful effects of emerging contaminants: pharmaceuticals, personal care products, and illicit drugs - Souza, Lorena da Silva; Fontes, Mayana Karoline [UNESP]; Pereira, Camilo Dias Seabra; DelValls Casillas, Tomas Angel (Elsevier, 2022)
Pharmaceuticals, personal care products, and illicit drugs (PPCPIDs) comprise a diverse group of chemicals recognized as contaminants of emerging concern. This class of contaminants has received growing global attentions due its potential for threatening drinking water safety and aquatic organisms. Considering the pathways by which they enter into the water environment, effluent from wastewater treatment plants (WWTPs) has been identified as an important source. Although nowadays it is mandatory in developed countries to perform sewage treatment to minimize the pollution of the receiving waters, there are many substances (e.g., antibiotics, hormones, cocaine) that are not efficiently removed in WWTPs. These compounds reach aquatic ecosystems and represent a risk to biota. This chapter aimed to share and discuss new research conducted nowadays on the impact of the CO2 acidification in bioavailability and toxicity of emerging organic contaminants such as PPCPIDs. New set of data and recent studies will be discussed and summarized in this chapter.
Keywords: Acidification methods; Chronic toxicity; Illicit drug; Personal care products; Pharmaceuticals; PPCPID